Influence of long-distance air transport conditions on horticultural product quality: Case study of fresh mango shipment from Thailand to France - Onrawee Laguerre; Steven Duret; Nattawut Chaomuang; Alain Denis; Evelyne Derens‐Bertheau; Pornkanya Mawilai; F.T. Ndoye; Thadchapong Pongsuttiyakorn; Samak Rakmae; Kraisuwit Srisawat; Panmanas Sirisomboon; Pimpen Pornchaloempong (International Journal of Refrigeration, 2023)
• Measured data of in-flight conditions revealed the decreasing trend of air and fruit temperatures. • Difference in mass loss of mangoes transported via direct and indirect flights was obviously detected. • Kinetic models could predict product temperature, mass loss and peel color change as a function of a supply chain scenario. • Stable ambient temperature and relative humidity are key factors determining the preservation of product quality . Four instrumented boxes of mangoes Mangifera indica L. cv. “Nam Dok Mai” were shipped from Bangkok, Thailand, to Paris, France, without control of the boxes’ positions on the aircraft. Two boxes were shipped via a direct flight and two boxes were shipped via an indirect flight. For each box, the internal air temperature, the external air temperature and relative humidity and surface temperature of two fruits were recorded throughout the supply chain from a packing house in Thailand to a storage room in France. A maximum fruit temperature of 33 °C (during transport from an orchard to the packing house) and a minimum fruit temperature of 8 °C (in a cold room of the logistics company following arrival at the airport in France via the indirect flight) were observed. The slight temperature difference between the air and the fruit surface temperature (< 1 °C on average) for both direct and indirect flights suggests that the air was stagnant inside the box and, thus conduction was the main heat transfer mode. Models of product temperature, mass loss, and peel color changes throughout the supply chain were developed. The numerical and the experimental values were in good agreement. These models were able to predict the product mass loss and peel color evolution as a function of a supply chain scenario.
Keywords: Postharvest Quality and Shelf Life Management; Plant Surface Properties and Treatments; Date Palm Research Studies